Evaluasi Pembelajaran Berbasis Digital untuk Meningkatkan Kualitas Hasil Belajar Siswa SD (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2026)
Rapid progress in information and communication technology has significantly influenced education, particularly in the assessment of student learning. This research aims to explore the use of digital assessment methods at SD Binekas Bandung and their role in improving educational standards. A qualitative descriptive methodology was utilized, which involved direct observation, interviews with the school’s administrators and teachers, and the collection of relevant documentation. The study was conducted on October 21, 2025. The findings indicate that SD Binekas has effectively integrated digital assessment instruments such as Google Forms, Quizizz, Wordwall, and smart boards. Teachers actively utilize these tools for both formative and summative assessments. Students showed a favorable response, reflecting heightened motivation and involvement. The identified advantages include more streamlined assessment processes, instant feedback, the ability to conduct statistical analyses, and enhanced digital skills among learners. However, several challenges remain, including dependence on internet connectivity, varying degrees of digital literacy among users, and obstacles in evaluating psychomotor skills. The implementation of digital assessments at SD Binekas has successfully improved the quality of teaching and learning through more efficient, engaging, and transparent assessment strategies.